eCM 2004
DOI: 10.22203/ecm.v007a01
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-engineered human asthmatic bronchial equivalents

Abstract: The isolation of human bronchial epithelial (HBEC) and fibroblastic cells (HBFC) from biopsies of asthmatic and non-asthmatic volunteers provided unique cellular materials to be used for the production of bioengineered bronchial equivalents (BE) in vitro. The HBEC are grown on a mesenchymal layer seeded with HBFC and the BE can be maintained for at least 15 days in culture. Under the BE culture conditions established previously, HBEC undergo differentiation into ciliated and goblet cells, within a pseudostrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…Several research groups, including our own, have recently demonstrated the advantages of three-dimensional airway co-culture models that provide an ECM and organization of a cellular community over traditional (two-dimensional, single-cell) culture models for recapitulating physiologic and pathophysiologic behavior (38)(39)(40)(41). Our model here additionally mimics the mechanical function of the smooth muscle cells by incorporating lateral and dynamic compression to the three-dimensional culture system over a long-term period.…”
mentioning
confidence: 99%
“…Several research groups, including our own, have recently demonstrated the advantages of three-dimensional airway co-culture models that provide an ECM and organization of a cellular community over traditional (two-dimensional, single-cell) culture models for recapitulating physiologic and pathophysiologic behavior (38)(39)(40)(41). Our model here additionally mimics the mechanical function of the smooth muscle cells by incorporating lateral and dynamic compression to the three-dimensional culture system over a long-term period.…”
mentioning
confidence: 99%
“…The utility of previously developed in vitro models for studying transepithelial transport-related phenomena is limited by the level of bronchial epithelial cell differentiation and ciliary function attainable (10 -12, 50, 51, 55). Culture conditions that were previously developed to promote epithelial differentiation towards a pseudostratified state include coculture with fibroblasts within a 3D matrix (1,11,50,51,63,64,75), the addition of specific factors to a serum-free media (15,27,55), and culture in ALI after epithelial cells have reached confluence (3,15,18,49,65). We further optimized the medium composition for ciliogenesis and cultured for 21 days at ALI.…”
Section: Discussionmentioning
confidence: 99%
“…Several biocompatible and biodegradable scaffolding materials have been explored for the engineering of 3-D lung tissues. Initial and obvious choices are natural ECM proteins such as collagen (29,71,145,146,191). However, due to its low mechanical properties in loose hydrogel configurations, collagen by itself is not load-bearing unless it is cross-linked or mechanically compressed, which may separately be relevant to the issue of reduced recellularization potential, and reduced flexibility of the scaffold for eventual use.…”
Section: L629mentioning
confidence: 99%